De la parole aux videos. Oralité, écriture et oralité médiatique dans la production culturelle Amazigh (Berbere) - Merolla, Daniela (Afrika Focus, 2005)
This article presents new directions in Tamazight/Berber artistic productions. The development of theatre, films and videos in Tamazight are set in the framework of the historical and literary background in the Maghreb and in the lands of Amazigh Diaspora. It also includes the interview with the video-maker and director Agouram Salout. Key Words: tamazight, berber, theatre, videos, film, taqbaylit, tarifit, tachelhit, new cultural production, writing, orality